The Muslim entrepreneur practices on halal supply chain management: A study in small enterprise - Abd Wakil, Najwa Alyaa; Abdul Latif, Mohd Syahiran; Mohd Sirajuddin, Mohd Dasuqkhi; Moidin, Shofiyyah; Said, Shahirah; Mohd Zahid, Emie Sylviana; Mazlan, Muslihah; Abd Rahim, Fathin Shahirah (Journal of Islamic, Social, Economics and Development, 2025)
The objective of this study is to understand the process of the practices for Halal supply chain management among Muslim entrepreneurs specifically in small enterprises. Moreover, this study is conducted based on qualitative methodology through interviews to better understand the practices of Halal supply chain management by the Muslim entrepreneur in their own business specifically in small enterprises. In addition, the findings of this study found that Halal supply chain management is built on avoiding direct contact with Haram, resolving contamination risks, and assuring compliance with Muslim customer perceptions. Product and market characteristics, in particular, are essential determinants in the management of Halal supply chains. A deeper awareness of the concepts for organizing the Halal supply chain among Muslim entrepreneurs is also essential. Apart from that, there is a lack of academic research in the actual practices of Halal supply chain management by the Muslim entrepreneur especially in small enterprises. This is due to the search in the Scopus database that there are only 20 papers that study Halal supply chain management and a few of these papers focus on the Muslim entrepreneur with small enterprises. Thus, this study provides the actual practices of the Halal supply chain management throughout the process of Halal products and additional knowledge specifically for Muslim entrepreneurs that involve the production of Halal products in small businesses.